Helios but not CD226, TIGIT and Foxp3 is a Potential Marker for CD4(+) Treg Cells in Patients with Rheumatoid Arthritis - Yang, Mengru (Cell Physiol Biochem, 2019)
BACKGROUND/AIMS: Rheumatoid arthritis (RA) is a progressive, chronic, even disabling systemic autoimmune disease. Imbalance between pathogenic immune cells and immunosuppressive cells is associated with the pathogenesis and development of RA and other autoimmune diseases. As Foxp3 is also expressed on activated CD4(+) cells in the presence of inflammation, the identification of Treg cells in patients with RA remains a challenge. METHODS: Comprehensive analyses were carried out by Flow cytometry. Expression of Helios, CD226, T cell immunoreceptor with Ig and ITIM domains clinical samples and healthy controls. RESULTS: We have systemically examined three potential markers, Helios, CD226 and TIGIT, that are possibly related to Treg identification, and found that Helios expression on CD4(+)Foxp3(+) cells was decreased and negatively correlated with the disease activity of RA patients, while CD226 and TIGIT both showed elevated expression levels in CD4(+)Foxp3(+) cells in RA patients and they were not associated with disease activity of RA patients. CONCLUSION: Taken together, our findings indicate that CD4(+)CD25(hi)CD127(low/-)Foxp3(+)Helios(+) may represent the real Treg cell population in patients with RA.